Terminação de cordeiros em pastagem cultivada de azevém (Lolium multiflorum Lam.) com diferentes níveis de suplementação com farelo de arroz integral - Simões, Robson Rodrigues (2016)
The study was conducted at Federal University of Santa Maria with aim of to evaluate the effect of levels of energetic supplementation of whole rice bran (Oriza Sativa) on characteristics of herbage production, performance, behavior intake, nutrients intakes, carcass characteristics, live weight components and qualitative and quantitative characteristics from lamb meat weaned of corriedale breed kept in continuous grazing under ryegrass pasture (Lolium multiflorum Lam.). 27 lambs were used and randomly distributed in nine paddocks and three treatments and three replications of area with three lambs per plot. The treatments (levels) were constituted by ryegrass pasture (RP), ryegrass pasture + 1% of live weight of supplement (RP + 1% of LW of SU) and ryegrass pasture + 2% of LW of supplement, (RP + 2% of LW of SU), beside calcitic limestone mixed with supplement and salt ad libitum. The slaughter criteria was the fix time for all treatments that was 50 days of grazing with 12 hours of fasting solid. After was evaluated the carcass characterists, LW components and lamb meat. The experimental design used was completely randomized in factorial design (3x2) and the datas were submitted analysis of variance at 5% significance and Tukey test was used for means comparison and also was used the PROC GLM (SAS, 2013). The use of levels of energetic supplementation of whole rice bran not influenced (P>0.05) on characterists of pasture and animal performance. However, there were differences (P<0.05) for ingestive behavior, for (levels and periods) for variables as leisure, grazing, supplementation, water intake and rumination. For nutrients intake there were differences (P<0.05) between levels for all variables analyzed. There were differences among periods from variables as CMSPA, CMOPD, CFDNPA e CFDNT. For characteristics of carcass occurried differences (P<0.05) for levels for perirenal fat, for meat quality the differences were between variable as crude protein, color of subcutaneous fat and (Longissimus dorsi) muscle.